Prenylated Chalcones as Anticancer Agents Against Castration-Resistant Prostate Cancer - Marcos Morales-Reyna; Elisa Elvira Figueroa-Angulo; José Espinoza-Hicks; Alejandro Camacho-Dávila; César López-Camarillo; Laura Isabel Vázquez-Carrillo; Alfonso Salgado-Aguayo; Ángeles Carlos-Reyes; Violeta Deyanira Álvarez-Jiménez; Jonathan Puente-Rivera; María Elizbeth Alvarez-Sánchez (Scientia Pharmaceutica)
Prenylated chalcones have garnered attention as potential anticancer agents due to their ability to modulate multiple cancer-related pathways. In this study, we synthesized and evaluated nine novel prenylated chalcone derivatives for their antiproliferative effects against castration-resistant prostate cancer (CRPC) cell lines, DU145 and PC3. Among these, compounds 6d and 7j demonstrated potent cytotoxic activity, with IC50 values comparable to cisplatin, and exhibited selective toxicity towards cancer cells over non-tumorigenic RWPE-1 cells. Mechanistic investigations revealed that these compounds induce apoptosis via mitochondrial membrane depolarization and increased late apoptotic events. Flow cytometry confirmed activation of both early and late apoptotic pathways. These findings highlight the potential of chalcone derivatives 6d and 7j as promising therapeutic candidates for CRPC treatment and support further development of chalcone-based molecules in precision oncology.